The (il)legality of unilateral sanctions in light of the inadequacy of humanitarian exemptions - Strauss, Michael J. (Journal of the Belarusian State University. International Relations, 2021)
This article argues that unilateral economic sanctions are unlawful because their design and implementation inherently result in violations of human rights that all states are obliged to respect, protect and fulfil under international law. In explaining this, it details the structural reasons why humanitarian exemptions are incapable of fully eliminating the problem. The article then considers the legality of imposing sanctions in the knowledge that human rights will be violated; whether such a violation must be intentional to constitute a breach of international law; and whether the principle of proportionality is relevant to a determination of the legality of the sanctions. In concluding that unilateral sanctions constitute an element of state conduct that has become increasingly widespread and frequent despite the damage they cause to human rights, the article presents three possible scenarios from which their legality might emerge: their entry into customary international law, which would imply an erosion of the obligations of states to respect and protect human rights; the development of a dedicated area of international law that encompasses sanctions to ensure that human rights are respected and protected when they are used; and the prospect for sanctions themselves to be reconceptualised and structured in a way that makes them benign with respect to human rights.
Keywords: unilateral sanctions; human rights; humanitarian exemptions; legality; effectiveness